Estimating Bobwhite Population Size by Direct Counts and the Lincoln Index - Ralph W. Dimmick; Forest E. Kellogg; Boyd L. Dearden (National Quail Symposium Proceedings, 2017)
Thirteen paired estimates of bobwhite (Colinus virginianus) populations were obtained using the Lincoln Index and a Walk Census on two study areas in Florida and one in Tennessee, Population densities ranged from 1,0 to 7,6 birds/ha as estimated by the Lincoln Index , Unadjusted estimates obtained by the Walk Census averaged 51 percent of those obtained by the Lincoln Index, The correlation coefficient (r) for the 13 paired estimates was 0,96, The linear relationship between the Walk Census and Lincoln Index estimates was defined by y = l,65x + 101.6, where y = Lincoln Index estimate and x = Walk Census estimate, The Lincoln Index gave an unbiased estimate of the "true" population; either adjusting the Walk Census estimates by doubling the count or using the predictive equation generally produced acceptable estimates of the "true" population,